Supercapacitor performance of corn stover-derived biocarbon produced from the solid co-products of a hydrothermal liquefaction process. (February 2021) - Shell, Katelyn M.; Rodene, Dylan D.; Amar, Vinod; Thakkar, Anuj; Maddipudi, Bharathkiran; Kumar, Sandeep; Shende, Rajesh; Gupta, Ram B.
Abstract: Biocarbon is obtained by the graphitization of biochar, a co-product in a novel integrated biorefinery concept that simultaneously produces C1–C3 acids, phenol, bio-oil, and biochar. The unhydrolyzed solids from the IBR are hydrothermally liquefied to obtain bio-oil and biochar coproducts. The biochar samples obtained from the HTL of UHS at different process conditions were low temperature thermally treated to remove volatile compounds, followed by a facile high temperature graphitization to biocarbon. Physical analyses showed the degree of graphitization directly effects pore volume. The UHS-SDC9 biochar produced at 275 °C, 40 psig, and 1 h of hydrothermal treatment exhibited the biocarbon with the best electrochemical performance having specific capacitance of 242 F g −1 at a scan rate of 5 mV s −1 and an energy density of 9.9 W h kg −1 . Statistical analysis was performed to correlate the IBR processing parameters to physical and electrochemical characteristics of the biocarbon obtained. Graphical abstract: Unlabelled Image Highlights: An integrated biorefinery process for corn stover biomass is demonstrated Hydrothermal liquefaction (HTL) of unhydrolyzed solids (UHS) at various parameters Facile one-step thermal activation process generated biocarbon for supercapacitors Specific capacitance of 242 F g −1 at 5 mV s −1 & power density of 9.9 Wh kg −1 in 2 M KOH Statistical modeling of HTL parameters in relation to electrochemical performance